2005
DOI: 10.1152/ajpgi.00168.2004
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Intestinal Phosphate Transport II. Metabolic acidosis stimulates Na+-dependent phosphate absorption and expression of the Na+-Pi cotransporter NaPi-IIb in small intestine

Abstract: During metabolic acidosis, P i serves as an important buffer to remove protons from the body. Pi is released from bone together with carbonate buffering protons in blood. In addition, in the kidney, the fractional excretion of phosphate is increased allowing for the excretion of more acid equivalents in urine. The role of intestinal P i absorption in providing Pi to buffer protons and compensating for loss from bone during metabolic acidosis has not been clarified yet. Inducing metabolic acidosis (NH 4Cl in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
2
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 29 publications
5
36
2
3
Order By: Relevance
“…The present finding of hyperphosphaturia in CMA rats is consistent with prior reports in human (16) and mouse mineral acidosis (24). However, the finding that intestinal P i uptake into small intestinal apical vesicles is increased in parallel with increased small intestinal NaPiIIb transporter protein in mice with CMA suggests that intestinal P i hyperabsorption may play a major role in the hyperphosphaturia of acidosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present finding of hyperphosphaturia in CMA rats is consistent with prior reports in human (16) and mouse mineral acidosis (24). However, the finding that intestinal P i uptake into small intestinal apical vesicles is increased in parallel with increased small intestinal NaPiIIb transporter protein in mice with CMA suggests that intestinal P i hyperabsorption may play a major role in the hyperphosphaturia of acidosis.…”
Section: Discussionsupporting
confidence: 92%
“…Cancellous microarchitecture was analyzed in vivo at the same skeletal location using CT (Viva CT40; Scanco Medical, Bassersdorf, Switzerland) (19,24). The scans were performed with the following instrument settings: 55 kV, 145 A, 300-ms integration time, 2,000 projections on 360°, 2048 charge-coupled device detector array, cone-beam reconstruction.…”
Section: Methodsmentioning
confidence: 99%
“…Mice that receive NH 4 Cl develop chronic metabolic acidosis that is characterized by a slight decrease in blood pH, a reduced serum HCO 3 Ϫ concentration, and, importantly, a low urine pH as substantiated in this study (24). Vennekens et al (31) recently demonstrated that extracellular protons inhibit TRPV5 in vitro by titrating glutamate 522 in the extracellular loop between the fifth putative transmembrane domain and the pore region as shown by Yeh et al (32).…”
Section: Discussionsupporting
confidence: 74%
“…NaPi-IIa is expressed in osteoclasts (37,53) and chondrocytes (62), whereas osteoblasts express both NaPi-IIa and NaPi-IIb (59). NaPi-IIb is responsible for transcellular P i absorption in the small intestine and is regulated by dietary P i (80) and metabolic acidosis (91). In the liver, NaPi-IIb is involved in the reabsorption of P i from primary hepatic bile (35).…”
Section: Slc34: Type II Na ϩ /P I Cotransporter Familymentioning
confidence: 99%